Development and Validation of a Discriminating In Vitro Dissolution Method for Oral Formulations Containing Satranidazole. (23rd April 2014) - Pawar, Harshal Ashok; Joshi, Pooja Rasiklal
Abstract : The development of a meaningful dissolution procedure for drug products with limited water solubility has been a challenge to the pharmaceutical industry. Satranidazole (BCS Class II drug) is a new nitroimidazole derivative with potent antiamoebic action. There is no official dissolution medium available in the literature. In the present study, parameters such as saturation solubility in different pH medium, dissolution behavior of formulations, influence of sink conditions, stability, and discriminatory effect of dissolution testing were studied for the selection of a proper dissolution medium. Results of solubility data revealed that solubility of Satranidazole decreases with an increase in pH. Satranidazole showed better sink condition in 0.1 N HCl as compared to other media. The drug and marketed formulations were stable in the dissolution media used. An agitation speed of 75 rpm showed a more discriminating drug release profile than 50 rpm. Using optimized dissolution parameters (paddle at 75 rpm, 900 mL 0.1 N HCl) greater than 80% of the label amount is released over 60 minutes. UV-spectroscopic method used was validated for the specificity, linearity, precision, robustness, and solution stability. The method was successfully applied to granular formulations and also to marketed tablets containing 300 mg Satranidazole.